Clinical management of pheochromocytoma and paraganglioma in Singapore: missed opportunities for genetic testing. Issue 5 (20th July 2017) - Chew, Winston Hong Wern; Courtney, Eliza; Lim, Kok Hing; Li, Shao Tzu; Chen, Yanni; Tan, Min Han; Chung, Alexander; Khoo, Joan; Loh, Amos; Soh, Shui Yen; Iyer, Prasad; Loh, Lih Ming; et al.
Abstract: Background: Pheochromocytomas and paragangliomas (PPGLs) are neuroendocrine tumors of the adrenal glands and paraganglia, occurring sporadically or as a range of hereditary tumor syndromes. About 30% of PPGLs are attributed to germline mutations. Clinical presentation, including localization, malignant potential, and age of onset, varies depending on the genetic background. Genetic testing for PPGLs is not well studied in Southeast Asia. We reviewed clinical management of PPGLs in Singapore, highlighting current gaps in clinical practice. Methods: Medical records of patients with PPGLs between 2005 and 2016 were reviewed. Diagnosis was confirmed histologically and stratified into sporadic or familial/syndromic (FS). Results: Twenty‐seven (21.8%) patients were referred to the Cancer Genetics Service (CGS). FS PPGLs (18.5%) and extra‐adrenal PPGLs (58.1%) incidences were higher than previous studies. Referrals were lower for sporadic PPGLs compared to FS PPGLs (3.7% vs. 100%). Referrals were highest at diagnosis age <20 years old (80%) and decreased with increasing age; ≥20–<40 years old (32.1%), ≥40–<60 years old (10.6%). Genetic testing was taken up in 12/27 (44.4%) patients of which 7/12 (58.3%, 3 SDHB, 2 SDHD, 2 VHL ) had germline mutations. Conclusion: Opportunities for genetic testing are frequently missed due to low referral rates in patients with apparently sporadic PPGLs, particularly between ages 20‐60. Abstract : Graph depicting distribution of genetic management of patients with pheochromocytoma and paraganglioma in Singapore.